Program Revitalisasi Pemberian Tablet Tambah Darah dalam Pencegahan Stunting di SMA Negeri 1 Kintamani - Luh Gede Pradnyawati (Warmadewa University Press, 2024)
Abstract Stunting is a growth disorder in children where the body length is shorter than that of children of the same age as a result of chronic malnutrition starting when the child is still in the womb. Malnutrition and anemia since adolescence have an impact on the incidence of stunting in one area. The government is carrying out efforts to prevent anemia in adolescents in order to prevent stunting in the form of the Teenage Girls' Blood Supplement Tablet Program (TTD Rematri) targeting girls aged 12-18 years. SMAN 1 Kintamani is one of the schools where TTD Rematri is implemented. Based on interviews with the person in charge of the program and with the implementation teacher at SMAN 1 Kintamani, it is known that the main problem that occurs is the very low level of compliance of female students in taking TTD which is caused by students' low knowledge about the TTD program and weak supervision of taking medication. Therefore, the proposed solution in assisting schools in implementing Rematri TTD at SMAN 1 Kintamani is: 1) increasing female students' knowledge about TTD through peer education, 2) increasing compliance with taking TTD through the use of teachers as medication taking supervisors (PMO), and 3) implement a medication monitoring system. The activities carried out in this mentoring are: 1) socialization of the program to leaders, teachers and female students of SMAN 1 Kintamani, 2) Training of peer educators, 3) Implementation of peer education, 4) provision of TTD with supervision by the teacher as PMO. The principal will supervise the implementation of the TTD program at school, the teacher will act as PMO, and the PMR (Youth Red Cross) students will act as peer educators. Evaluation is carried out after training and after the program is completed. The result of this service is that the revitalization program for providing blood supplement tablets at SMAN 1 Kintamani is running smoothly. From this mentoring program, 75% of female students experienced increased knowledge about TTD and adhered to taking medication. Keywords: Program, revitalization, blood supplement tablets, stunting, SMAN 1 Kintamani